User Interface Analysis of Gapura Universitas Multimedia Nusantara Website - Dara Shafira Zahra; Wella Wella; Aditya Satyagraha (Universitas Multimedia Nusantara, 2021)
The user interface (UI) of the Gapura site is proven to have various problems such as a poor visual hierarchy, UI that confuses its users, and UI that are considered unattractive by users. These things result in the poor feedback of its users. This study aims to examine the problems in the Gapura site by using the guidelines of the e-book published by UXPin,